Government incentives directed towards foreign direct investment: a case of Central and Eastern Europe - Ginevičius, Romualdas; Šimelytė, Agnė (Journal of Business Economics and Management, 2011)
This article examines the government incentives towards foreign direct investments (further – FDI) of Central and Eastern Europe countries by evaluating the external influencing factors of foreign investment. It is argued that the major incentive affecting FDI inflows involves more fiscal than financial incentives. Tax deduction is considered to be the most significant influencing factor on attracting FDI. Hence, the empirical analysis is based on exogenous variables. The empirical model was used to determine causal relationship between macroeconomic variables and FDI intensity in Central and Eastern European countries. The article introduces some policy recommendation for the increase of FDI intensity in Central and Eastern Europe.Article in English.Užsienio investicijų intensyvinimo priemonių taikymo Rytų ir Centrinėje Europoje analizėSantrauka. Straipsnyje nagrinėjama, kaip užsienio investicijų priemonės taikomos Centrinės ir Rytų Europos šalyse. Vertinami išoriniai užsienio investicijas lemiantys veiksniai, teigiama, kad TUI įplaukas skatina daugiau mokesčių nei finansinės paskatos. Tačiau laikomasi nuomonės, kad mokesčių lengvatos – vie-na pagrindinių priežasčių, lemiančių TUI įplaukas. Empirinis modelis pagrįstas mažiausiųjų kvadratų metodu, kuriuo nustatomas priežastinis sąryšis tarp makroekonominių rodiklių ir TUI intensyvumo. Straipsnyje pateikiamos kai kurios politinės įžvalgos, kurių taikymas padidintų tiesioginių užsienio investicijų intensyvumą Centrinėje ir Rytų Europoje.Reikšminiai žodžiai: iniciatyvos, tiesioginės užsienio investicijos, TUI apibrėžiantys veiksniai, Airijos modelis, TKC modelis.